Hubungan Health Locus Of Control Dengan Self-Care Behavior Pasien Diabetes Mellitus Tipe 2 - Baiq Ruli Fatmawati; Zaenal Arifin; Dewi Nur Sukma Purqoti; Ilham Ilham (STIKes Surya Global Yogyakarta, 2023)
Background: Diabetes Mellitus is a chronic metabolic disease characterized by an increase in glucose levels in the blood, so it is required to carry out a series of DM management independently with the aim of avoiding the risk of complications and controlling glucose levels in the blood. Health locus of control is a belief in controlling the good and bad of a person's health behavior.The objective: This research is to determine the relationship between health locus of control and self-care behavior of Diabetes Mellitus type 2 patients in working area of Penimbung public health centerMethods: The method uses a cross-sectional study design. The sample consisted of 81 respondents with purposive sampling method. Results: The results of the spearman rank correlation test showed that there was a significant relationship with positive strength between HLoC and self-care behavior (ρ-value 0.005).Conclusion: There was a significant relationship between the health locus of control and the self-care behavior of patients with Diabetes Meilitus type 2.Keywords: DM type 2; Health Locus Of Control; self-care behavior